Good University Governance of PTKIN Public Services Agency in Indonesia - Ismawati Haribowo; Susi Dwi Mulyani (Universitas Pendidikan Ganesha, 2021)
This study aims to prove the effect of the role of internal auditors, organizational commitment, on good university governance and its implications for the quality of financial reports at PTKIN-BLU. The independent variables of this study are good university governance and the quality of financial reports, while the dependent variable in this study is the role of internal auditors and organizational commitment. The sample of this study used data from 60 respondents from the Head of Study Programs from the State Islamic University (UIN) in Indonesia. Data collection has been carried out since 2019 using the questionnaire survey method. After the data is collected, data analysis is carried out using SmartPLS software. This study concludes that the role of the internal audit unit, organizational commitment has a positive and significant effect on good university governance. Good University Governance has a positive and significant effect on the quality of BLU financial reports. If the implementation of good university governance is carried out consistently, the quality of financial reports will be better.